Attentive amelioration: developing and evaluating an applied mindfulness programme for psychologists - McGarvie, Susan (Rhodes University, Faculty of Humanities, Department of Psychology, 2020)
It is readily accepted that healthcare in many third world countries is in crisis, but interestingly, even in wealthy first world countries, many healthcare systems are stretched to their limits, as fewer people choose to follow a career in healthcare and more staff members struggle under the pressures of an overextended system (Krasner, et al., 2009). Ways to improve healthcare practitioner wellbeing is thus a relevant and widely investigated topic (McCann et al., 2013), which has, until recently, been aimed at reducing the negative symptoms associated with poor wellbeing, such as stress and burnout. More recently, there has been burgeoning interest in the effects and potential benefits of mindfulness practice to wellbeing, especially in developed English-speaking countries like the UK, Canada, USA, Australia, as well as in Europe. The aim of this study was to contribute to this body of literature by proposing a more personalised and person-centred means to support and improve wellbeing. It was guided by an overarching research question, about the benefits of a mindfulness-based wellness course for practicing psychologists. This study is a mixed-methods narrative inquiry which employs both Action Research (AR) and Programme Evaluation methods. It involved the design, implementation and evaluation of a mindful-wellness programme, subsequently named the Attentive Amelioration programme. Ten participants were purposively recruited and enrolled in the programme, which ran over eight weeks and included coaching and blended learning facilitation methods, including: an introductory workshop (with a pedagogical mix of lecture, group discussion, practical activities, learners manual and YouTube clips), individual and group coaching sessions, and an online learning programme. The findings suggest that psychologists do experience a great deal of stress and perceived levels of burnout are high, even if the scores on the pre- and post- intervention self-assessment scales do not entirely support this perception. This study found that participants were open to and engaged with mindfulness training and practice and sustained that practice for several months post-intervention. Finally, overall findings suggest that while the Attentive Amelioration programme was effective as a means to cultivate and develop mindfulness, self-compassion and overall wellbeing in the short-term, further investigation is required to determine the sustainability of the effects over the long-term. The findings of this study support the overall aims of the study in that it has found that the participating psychologists found the Attentive Amelioration programme to be beneficial, supportive and even therapeutic. By contributing to and supporting findings of existing research, that suggest that a mindfulness-based coaching programme would be beneficial to psychologist wellbeing and therapeutic proficiency, it serves to advocate for mindfulness as a means to improve and sustain psychologist wellbeing..
Keywords: Attentive Amelioration Programme; Mindfulness (Psychology); Psychotherapy -- Practice; Counseling -- Practice; Medical professionals -- Mental health